2019
DOI: 10.3390/geosciences9100426
|View full text |Cite
|
Sign up to set email alerts
|

Six Years Temperature Monitoring Using Fibre-Optic Sensors in a Bioreactor Landfill

Abstract: Temperature is a relevant physical parameter to monitor the biodegradation phases of waste mass. Irstea and the landfill operator SAS Les Champs Jouault have been collaborating since 2011 to study the temporal evolution and the spatial distribution of temperature in a municipal solid waste cell. Using distributed temperature sensing technology, optical fibres were installed in waste mass composed of household waste and industrial waste at different depths during the landfilling period. Temperature distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Yoshida and Rowe 19 found that the waste temperature began to decrease approximately 10 years later. Magyar and Faitli 28 summarized the temperature variations of different filling age wastes in the Gyal landfill, and proposed a trend function for the temperature variation; Moreau et al 29 found that the waste temperature in the Caen landfill increased significantly during the waste placement period, but the waste temperature decreased after the closure of the landfill. The stratification of the new and old waste existed in an operating landfill 24 , 25 , 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida and Rowe 19 found that the waste temperature began to decrease approximately 10 years later. Magyar and Faitli 28 summarized the temperature variations of different filling age wastes in the Gyal landfill, and proposed a trend function for the temperature variation; Moreau et al 29 found that the waste temperature in the Caen landfill increased significantly during the waste placement period, but the waste temperature decreased after the closure of the landfill. The stratification of the new and old waste existed in an operating landfill 24 , 25 , 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have obtained the temperature distribution in landfills using numerical 19 , 29 , 32 44 and analytical 45 , 46 calculations. The landfills in these studies were generally regarded as landfills with a homogeneously unsaturated waste layer 19 , 29 , 32 46 or a continuously placed waste layer 19 , 32 , 33 , 35 , 36 , 39 43 , 45 , 46 . The current theoretical method can be used to evaluate the temperature distribution in most landfills.…”
Section: Introductionmentioning
confidence: 99%